2016
DOI: 10.1371/journal.ppat.1005661
|View full text |Cite
|
Sign up to set email alerts
|

Exhaustion of Activated CD8 T Cells Predicts Disease Progression in Primary HIV-1 Infection

Abstract: The rate at which HIV-1 infected individuals progress to AIDS is highly variable and impacted by T cell immunity. CD8 T cell inhibitory molecules are up-regulated in HIV-1 infection and associate with immune dysfunction. We evaluated participants (n = 122) recruited to the SPARTAC randomised clinical trial to determine whether CD8 T cell exhaustion markers PD-1, Lag-3 and Tim-3 were associated with immune activation and disease progression. Expression of PD-1, Tim-3, Lag-3 and CD38 on CD8 T cells from the clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
141
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(155 citation statements)
references
References 42 publications
8
141
0
1
Order By: Relevance
“…PD-1 has a central role in virus-specific CD8 T-cell exhaustion, it is upregulated in most CD8 T-cell populations during HIV infection and correlates with the level of CD8 T-cell exhaustion and with disease progression. [172][173] Several studies on animal models showed how PD-1 blockade was able to enhance proliferation of CD4 and CD8 T-cells, especially HIV-specific clones; moreover, an increased proliferation of resting memory B-cells and a reduction in microbial translocation were also demonstrated in animals treated with anti-PD-1 antibodies. 174 Other potential immune checkpoints target for immune intervention may be CTLA-4, Lag-3, Tim-3 and TIGIT and several investigators are exploring therapeutic options directed at these molecules.…”
Section: New Treatment Strategies and Immunotherapy In Aging Hiv Patimentioning
confidence: 99%
“…PD-1 has a central role in virus-specific CD8 T-cell exhaustion, it is upregulated in most CD8 T-cell populations during HIV infection and correlates with the level of CD8 T-cell exhaustion and with disease progression. [172][173] Several studies on animal models showed how PD-1 blockade was able to enhance proliferation of CD4 and CD8 T-cells, especially HIV-specific clones; moreover, an increased proliferation of resting memory B-cells and a reduction in microbial translocation were also demonstrated in animals treated with anti-PD-1 antibodies. 174 Other potential immune checkpoints target for immune intervention may be CTLA-4, Lag-3, Tim-3 and TIGIT and several investigators are exploring therapeutic options directed at these molecules.…”
Section: New Treatment Strategies and Immunotherapy In Aging Hiv Patimentioning
confidence: 99%
“…In the absence of ART, increased expression of PD-1 was associated with accelerated decline in CD4 + T cells following acute infection 48 and untreated chronic infection 36 . Following ART, PD-1 expression on CD8 + T cells has been associated with impaired CD4 + T cell immune reconstitution 49 microvascular disease 50 , elevated oxidised high and low density lipoproteins 51 and a shorter time to viral rebound once ART was stopped 52 .…”
Section: Introductionmentioning
confidence: 97%
“…However, when the immune system fails to eradicate cancer or clear stubborn infections, prolonged antigenic stimulation may lead to T CD8 functional impairments, including exhaustion and anergy (14). Exhausted or anergic T CD8 are often unable to secrete effector cytokines or launch optimal proliferative and cytotoxic responses to cognate Ags, which may compromise host defense mechanisms, positive clinical outcomes or even survival (57). …”
Section: Introductionmentioning
confidence: 99%